2009
DOI: 10.1111/j.1467-9922.2009.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Subject‐Object Ambiguities in the L2: A Self‐Paced Reading Study With German L2 Learners of Dutch

Abstract: The results of two self-paced reading experiments are reported, which investigated the online processing of subject-object ambiguities in Dutch relative clause constructions like Dat is de vrouw die de meisjes heeft/hebben gezien by German advanced second language (L2) learners of Dutch. Native speakers of both Dutch and German have been shown to have a preference for a subject versus an object reading of such temporarily ambiguous sentences, and so we provided an ideal opportunity for the transfer of first la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
106
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 52 publications
(68 reference statements)
13
106
2
1
Order By: Relevance
“…In contrast, native speakers showed the same effect at both SOAs (Ito et al, 2016). Since non-native speakers normally read more slowly than native speakers (Havik et al, 2009;Hopp, 2009), the longer 700 ms SOA is perhaps more likely to allow nonnative speakers to read at a comfortable pace. Therefore, we hypothesised that non-native speakers may show an N400 effect for unexpected nouns similarly to native speakers in Experiment 2.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, native speakers showed the same effect at both SOAs (Ito et al, 2016). Since non-native speakers normally read more slowly than native speakers (Havik et al, 2009;Hopp, 2009), the longer 700 ms SOA is perhaps more likely to allow nonnative speakers to read at a comfortable pace. Therefore, we hypothesised that non-native speakers may show an N400 effect for unexpected nouns similarly to native speakers in Experiment 2.…”
Section: Methodsmentioning
confidence: 87%
“…the use of information as soon as it becomes available), the first being a possible mechanism by which rapid, "predictive" computation of the context occurs, and the second being a processing heuristic that describes the computational architecture required to achieve language processing in real time (Altmann & Mirković, 2009). One reason that effective incremental use of information may be difficult to achieve for non-native speakers is that they read more slowly and more effortfully than native speakers (Clahsen & Felser, 2006;Havik, Roberts, Van Hout, Schreuder, & Haverkort, 2009). As a result, non-native speakers may have fewer cognitive resources available to construct a rich mental representation of the context in an online fashion, rendering the prediction of upcoming information based on that context less likely (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that these L2 learners were more sensitive to gender agreement violations with increasing WM capacity, suggesting that WM capacity can be a reliable predictor of L2 learners' sensitivity to agreement violations between adjacent words, at least for within-phrase agreement dependencies. Havik et al (2009) also report WM effects in their study on the processing of subject-object relative clause ambiguities by German L2 learners of Dutch, where verbal agreement disambiguated between the two types of clauses. The researchers manipulated the length of agreement dependencies, such that an adverbial phrase intervened or did not intervene between the second noun in the relative clause and the embedded verb (e. g., Daar is de machinist die de conducteurs [na het ongeluk met de trein] heeft/hebben bevrijd uit het brandende treinstel 'That is the engine driver who [after the accident with the train] has saved the guards/who the guards after the accident with the train have saved from the burning train-carriage').…”
Section: The Role Of Working Memory In L2 Processingmentioning
confidence: 99%
“…For example, Miyake and Friedman (1998) reported that WM correlated with Japanese-English learners' comprehension and cue preference when processing L2 syntactically complex sentences. Similarly, Havik, Roberts, van Hout, Schreuder, and Haverkort (2009) found that WM predicted German-Dutch learners' L2 processing of short-and long-subject and object relative clauses (only the high-span learners preferred to process object as subject short clauses like native Dutch speakers). In another self-paced reading study, Dussias and Piñar (2010) concluded that Chinese-English learners and English native speakers showed subject-object parsing asymmetries when processing long-distance wh-questions, but that only the high-span learners resembled the English controls when using plausibility information to facilitate recovery from initial misparses.…”
Section: Working Memory and Processing Of L2 Morphology And Syntaxmentioning
confidence: 99%